An Unusual Example of Asperigillus Species Lung Disease - Richard L Pardy; Martha Grymaloski; Blair AM Walker (Canadian Respiratory Journal)
A 37-year-old man developed persistent hemoptysis after sustaining a gunshot wound to the right shoulder and lung. A right upper lobectomy was performed, in which Aspergillus species microorganisms were identified within retained bullet fragments. The role of infected bullet fragments in the pathogenesis of hemoptysis in this patient is discussed.